PROGRAM KKN BALEK KAMPUNG PENGABDIAN KEPADA MASYARAKAT MELALUI PENINGKATAN MINAT BELAJAR SISWA DI KELURAHAN LANGGINI PADA MASA ENDEMI - Zulkarnaini Zulkarnaini; Adelia Putri2; Faraditha Selviana Tendun; Annisa Fadhilah Hadi; Bunga Yefita Gustriani; Fazry Alhadi Kamal; Hilda Mulyani; Lia Fitridayani; Rahma Resta; Rahmi Resti; Satria Anggara (Universitas Pahlawan Tuanku Tambusai, 2022)
Real Work Lecture (KKN) is a tangible manifestation of the duties of lecturers and students in implementing the Tri Dharma of Higher Education, namely the service aspect. Through community service activities in Langgini Village, there is a synergy between universities and the community as a form of democratic knowledge. The purpose of this service is to increase student interest in learning during endemic times to help the government in educating the nation's children. The method used in 3 stages, namely the planning, implementation and evaluation stages. The service is carried out through activities: tutoring using the ACTION learning method, ranking one competition, healthy exercise, and donating books and trash cans. The results of the service provide an overview of increasing enthusiasm, increasing understanding, and increasing student interest in reading and learning at Public Elementary School 017 Langgini. Keywords : KKN, service, education, interest in learning